Integrating local services for individuals in vulnerable situations (OECD Local Economic and Employment Development (LEED) Papers, 2023)
Governments at all levels are looking for new and innovative ways to include individuals in vulnerable situations such as youth, migrants, persons with disabilities and families facing multiple challenges, in the labour market and in society more generally. This paper explores integration of employment services with other services (e.g. social, health and housing) at the local level as one promising way for governments to provide more effective support that is holistic and person-centred and be more efficient in public spending. The paper analyses different forms of local service integration, the possible benefits, and the particular roles subnational governments can play in service integration reforms - ranging from national public employment service-led reforms to more locally driven reforms. The paper also analyses the barriers to service integration and proposes future work to strengthen local service integration